The development of a preliminary ultrasonographic scoring system for features of hand osteoarthritis. Issue 5 (17th August 2007) - Keen, H I; Lavie, F; Wakefield, R J; D'Agostino, M-A; Hammer, H Berner; Hensor, E; Pendleton, A; Kane, D; Guerini, H; Schueller-Weidekamm, C; Kortekaas, M C; Birrel, F; et al.
Abstract : Objectives: Painful osteoarthritis (OA) of the hand is common and a validated ultrasound (US) scoring system would be valuable for epidemiological and therapeutic outcome studies. US is increasingly used to assess peripheral joints, though most of the US focus in rheumatic diseases has been on rheumatoid arthritis. We aimed to develop a preliminary US hand OA scoring system, initially focusing on relevant pathological features with potentially high reliability. Methods: A group of experts in the fields of OA, US and novel tool development agreed on domains and suggested scaling of the items to be used in US hand OA scoring systems. A multi-observer reliability exercise was then performed to evaluate the draft items. Results: Synovitis (grey scale and Power Doppler) and osteophytes (representing activity and damage domains) were included and evaluated as the initial components of the scoring system. All three features were evaluated for their presence/absence and if present were scored using a 1–3 scale. The reliability exercise demonstrated intra-reader κ values of 0.444–1.0, 0.211–1.0 and 0.087–1.0 for grey scale synovitis, power Doppler and osteophytes respectively. Inter-reader reliability κ values were 0.398, 0.327 and 0.530 grey-scale synovitis, power Doppler and osteophytes respectively. Without extensive standardisation, both intra- and inter-reader reliability were moderately good. Conclusions: The draft scoring system demonstrated substantive to almost perfect percentage exact agreement on the presence/absence of the selected OA features and moderate to substantive percentage exact agreement on semi-quantitative grading. This preliminary process provides a good basis from which to further develop an US outcome tool for hand OA that has the potential to be utilised in multicentre clinical trials.